2015
DOI: 10.1089/jmf.2014.3229
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Inhibits Platelet-Derived Growth Factor-BB-Induced Proliferation and Migration in Vascular Smooth Muscle Cells

Abstract: The proliferation and migration of vascular smooth muscle cells (VSMCs) in blood vessels are important in the pathogenesis of vascular disorders such as atherosclerosis and restenosis. Piperine, a major component of black pepper, has antioxidant, anticancer, and anti-inflammatory activity. However, the antiatherosclerotic effects of piperine have not been investigated. In this study, the effects of piperine on platelet-derived growth factor (PDGF)-BB-induced proliferation and migration of VSMCs were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…PDGF, mainly expressed in VSMCs and endothelial cells, promote mitosis and play an important role in the proliferation of VSMCs [6][7][8]37]. The binding of PDGF-BB, a subtype of PDGF released from injured vessels, to its receptor can trigger the activation of downstream and then contribute significantly to VSMCs proliferation [9][10][11][12]. In this paper, PDGF-BB could effectively induce MOVAS proliferation, which was consistent with the previous studies reported.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PDGF, mainly expressed in VSMCs and endothelial cells, promote mitosis and play an important role in the proliferation of VSMCs [6][7][8]37]. The binding of PDGF-BB, a subtype of PDGF released from injured vessels, to its receptor can trigger the activation of downstream and then contribute significantly to VSMCs proliferation [9][10][11][12]. In this paper, PDGF-BB could effectively induce MOVAS proliferation, which was consistent with the previous studies reported.…”
Section: Discussionsupporting
confidence: 88%
“…Platelet-Derived Growth Factor (PDGF) is an important regulator that stimulates the proliferation of VSMCs [6][7][8]. The binding of PDGF-BB, a subtype of PDGF, to its receptor triggers the activation of downstream signaling molecules such as Mitogen-Activated Protein Kinases (MAPKs) to promote VSMCs proliferation and growth [9][10][11][12][13]. Therefore, preventing the PDGF-BB induced VSMCs proliferation might be a promising strategy for treating the development of neointima in atherosclerosis and post-angioplasty restenosis in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results did not demonstrate any differences in the area fraction of α-SMA + SMCs in 2-week specimens, but did identify decreased SMC proliferation in the PGDF-KO group. The decreased proliferation in PGDF-KO mice is consistent with literature demonstrating the paracrine role of PDGF in promoting SMC migration and proliferation [10,[22][23][24][25]. One potential reason that no difference was observed in the total quantity of SMCs between the two groups is that we specifically targeted only the PDGF-B subtype.…”
Section: Myeloid Cell Pdgf-b and Tevg Neotissue Development Research Arsupporting
confidence: 89%
“…The main constituent piperine is reported to enhance drug bioavailability and to modulate GABA A receptors, besides various other pharmacological activities, including analgesic, anti-inflammatory, anti-pyretic, anti-convulsive, anti-oxidant, anti-depressant, anti-apoptotic, anti-cancer, and anti-viral properties [12,[19][20][21]. In this study, we identified piperine (1) to be a promising inhibitor of VSMC proliferation, which was very recently also described by others [22]. We used piperine as lead compound to synthesize derivatives thereof and isolated structurally related amides from the fruits of P. nigrum to deduce a qualitative SAR with regard to the anti-proliferative effect in VSMCs.…”
supporting
confidence: 64%
“…All ). In addition to the isolated compounds, 15 further congeners were synthesized (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). All piperine analogues were subjected to cell-based assays.…”
mentioning
confidence: 99%